Give or take: thoughts on museum collections as working tools and their connection with human beings (Cadernos de Sociomuseologia, 2010)
This paper proposes a look at museums from the perspective of sociomuseology, an area of research and practice under development in countries such as Portugal, Brazil and Spain. Sociomuseology was born from the Latin new museology tradition and is closely connected with the International Movement for a New Museology (MINOM/ICOM). The Lusofona University in Lisbon offers MA and PhD programmes in Sociomuseology. The University supports a research centre in Sociomuseology and publishes the journals Cadernos de Sociomuseologia, in Portuguese, and Sociomuseology, in English (for more information see http://tercud.ulusofona.pt.). Sociomuseology concerns the study of the social role of museums and of the continuous changes in society that frame their trajectories. The practice of sociomuseologists is based on their work with the different dimensions of social and community development from ecomuseums to networking and other ways of organizing social action in the 21st century in which heritage plays a strategic role.